PENGARUH METODE BERCERITA DENGAN MEDIA BIGBOOK TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN DI SPS AZ-ZAHRA KELURAHAN SUKAMULIA KECAMATAN SAIL KOTA PEKANBARU - Endang Ratna Susilawati; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This study aims to determine how much influence the Storytelling method using Bigbook for listening skills of children aged 5-6 years in the SPS Az-Zahra Village Sukamulia District of Sail Pekanbaru. This study consists of two variables: Bigbook and Observing Capabilities. The hypothesis of this study are as follows: Method Tells the Big Book Media can improve the ability of Listening Childhood 5-6 Years On SPS Az-Zahra, Village Sukamulia, District Sail, Pekanbaru